Adsorption of Imazethapyr from Aqueous Solution on Activated Carbon - Diouri, N.; Guessous, A.; El Kacemi, K.; El Azzouzi, M.; El Hourch, A. (Asian Journal of Chemistry, 2010)
The removal of pesticide imazethapyr from wastewater under different batch experimental conditions, using an activated carbon was investigated. The pesticide under study was imazethapyr which is a well known herbicide in Moroccan agriculture. The adsorbent was activated carbon. It was determined that the adsorption of imazethapyr was slightly pH dependent. Different experimental parameters like initial pH, contact time and initial concentration on the adsorption of imazethapyr were evaluated. It was found that the rate of sorption of imazethapyr onto activated carbon is very fast with almost 94 % adsorption taking place in the first 10 min at pH = 3. The applicability of the Langmuir isotherm for the present system has been evaluated at different concentrations.